Molecular Docking and Interaction of Anthocyanin Derivatives in Regulating Hippo-taz Pathway for Renal Injuries - Hannah Raji; Oswitha Dsouza; Freeda Princy Dsouza (International Journal of Genetic Modifications and Recombinations, 2024)
Introduction: The Hippo pathway plays a pivotal role in renal disease, with Yes-associated protein (YAP) exhibiting promise for combined treatments. The crucial evaluation of YAP-targeted drug safety and efficacy through preclinical studies is imperative. Additionally, α-SMA and SMAD3 emerge as potential therapeutic targets in renal fibrosis, driving ongoing research toward innovative interventions. Materials and Methods: In the systematic identification of therapeutic secondary metabolites, Anthocyanin derivatives were methodically retrieved from the IMPPAT database. Ten distinct compounds underwent curation, and their molecular structures were systematically acquired. Molecular targets, including YAP, TGF-β1, SMAD3, and α-SMA, were precisely identified. Three- dimensional structures were meticulously sourced from the PDB and underwent purification. The process of molecular docking, facilitated by PyRx, coupled with a comprehensive in silico evaluation of ADMET properties, enhances our understanding of the therapeutic potential of Anthocyanin derivatives, with the ultimate goal of streamlining drug discovery processes. Results: The ligands sourced from the IMPPAT database underwent a stringent molecular docking process to validate structural integrity. The confirmation of protein suitability for docking was achieved through hydropathy analysis and Z-score plots. Notably, Alpha-boswellic acid demonstrated superior binding affinity, exhibiting significant promise for therapeutic applications. Additionally, the systematic analysis of Anthocyanin phytocompounds for ADMET properties revealed distinct bioactivity, providing valuable guidance for potential drug development. Conclusion: To summarize, the exploration of intricate interactions between the Hippo pathway and renal diseases presents novel prospects for targeted therapeutic interventions. Whether through YAP-targeted drugs, the modulation of α-SMA and SMAD3, or the incorporation of flavonoids, the scientific insights not only enhance our comprehension of fundamental molecular mechanisms governing renal health but also hold the promise of substantial advancements in the field of renal disease treatments.
Keywords: Anti-inflammatory; Hippo- Transcriptional co-activator with PDZ- binding motif; Suppressor of Mothers against Decapentaplegic 3; Transforming growth factor beta 1-β1; Yes-Associated Protein; α- smooth muscle actin